An investigation into the Intercultural Competence, Self-awareness, and Well-being among Arabic-Speaking Immigrants in Finland - Al Khuja, Hateem; Björkqvist Kaj (Technium Social Sciences Journal, 2023)
The aim of this study is twofold. First, explore the relationship between intercultural competence, and self-awareness and psychological well-being among the Arabic-speaking immigrant population in Finland; and second, compare the results of this study with a previous one conducted with Syrian refugees in Germany, with exactly the same methodology The intercultural competence of Arabic-speaking immigrants in Finland were evaluated to uncover the patterns and behaviours they exhibit in a foreign culture. In total, 358 respondents completed the questionnaire, the gender split was 36.6% female (131) and 63.4% male (227). The average age of the respondents was 34 years (Mage = 34.7, SD = 11.6). To assess intercultural competence, the APTOC, a 15-item scale with three main subscales (Openness to Other Cultures, Global Mindset, and Narrow Mindset), was used. The Self-reflection and Insight Scale was used to assess private self-awareness. The Brief Symptom Inventory’s three subscales of depression, anxiety, and hostility were used to assess well-being. While Openness to Other Cultures and Global Mindset were found to be positively related to Self-reflection, Narrow Mindset was found to be negatively related to Self-reflection and positively related to Insight, Depression, Anxiety, and Hostility. Additionally, the findings reveal significant differences between this study’s results and those of a previous study conducted in Germany, particularly concerning the length of stay in the host country and the effect of Openness to Other Cultures and Anxiety. These differences may inform the creation of programs and interventions aimed at improving intercultural competence and well-being among this population.